UPAYA MENINGKATKAN HASIL BELAJAR SISWA TERHADAP MATERI SIKLUS HIDUP HEWAN MELALUI PEMBELAJARAN COOPERATIVE LEARNING TIPE STAD PADA SISWA KELAS III SDN 4 KLEGEN - Hanifatur Rosyidah; Dia Rahmaton; Ramuna Eka Putri; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to improve the learning outcomes of grade III students in the subject of science on the animal life cycle material in grade III students of SDN 04 Klegen, Madiun City through the STAD type Cooperative Learning learning model on the animal life cycle material. The type of research conducted is Classroom Action Research (CAR). This study was conducted in two cycles to determine the improvement in student learning outcomes. Each cycle consists of one meeting with the following learning stages. Data collection techniques used observation, interviews with teachers, observations during learning and final evaluations for students based on the results of the pre-test and post-test. The results of the study showed that the use of the STAD type cooperative learning model in science learning on the animal life cycle material can significantly improve student learning outcomes. Students showed an increase in learning outcomes and also increased involvement and motivation to learn. The results of the study in the pre-cycle showed an average score of 48 with a percentage of 48%, while in cycle 1 the average increased to 68 with a percentage of 68%, and in cycle 2 the average reached 85 with a percentage of 85% for students whose scores were above the KKM, based on the results of the study, the application of the STAD type cooperative learning model can improve student learning outcomes in the subject of science on the animal life cycle material.